The automorphism groups of non-edge transitive rose window graphs - Dobson, Edward (Ars mathematica contemporanea, 2015)
In this paper, we determine the full automorphism groups of rose window graphs that are not edge-transitive. As the full automorphism groups of edge-transitive rose window graphs have been determined, this complete the problem of calculating the full automorphism group of rose window graphs. As a corollary, we determine which rose window graphs are vertex-transitive. Finally, we determine the isomorphism classes of non-edge-transitive rose window graphs.
Keywords: automorphism group; grupa automorfizmov; isomorphism problem; problem izomorfizma; rose window graphs; rozetni grafi; vertex-transitive graph; vozlično tranzitivni grafi